2010
DOI: 10.1038/labinvest.2010.126
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between microRNA expression levels and clinical parameters associated with chronic hepatitis C viral infection in humans

Abstract: MicroRNAs (miRNAs) are small RNAs that regulate gene expression pathways. Previous studies have shown interactions between hepatitis C virus (HCV) and host miRNAs. We measured miR-122 and miR-21 levels in HCV-infected human liver biopsies relative to uninfected human livers and correlated these with clinical patient data. miR-122 is required for HCV replication in vitro, and miR-21 is involved in cellular proliferation and tumorigenesis. We found that miR-21 expression correlated with viral load, fibrosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
160
5
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(184 citation statements)
references
References 48 publications
15
160
5
4
Order By: Relevance
“…This miRNA is the first to be studied as a therapeutic tool and other two studies (Connolly et al, 2008;Zhu et al, 2011) have shown that the transfection of tumor cells with antisense oligonucleotides specific for mir-21 leads to a reduction of the cell growth and survival. Likewise studies by Xu et al (2011a), Bihrer et al (2011), Marquez et al (2010 have shown that serum levels of miR-21 are increased with a progressive course from chronic hepatitis to cirrhosis and hepatocellular carcinoma. Multivariate analyses demonstrate that the only parameters to be associated with this miRNA are histological necroinflammation and viral load.…”
Section: Mir-21mentioning
confidence: 86%
“…This miRNA is the first to be studied as a therapeutic tool and other two studies (Connolly et al, 2008;Zhu et al, 2011) have shown that the transfection of tumor cells with antisense oligonucleotides specific for mir-21 leads to a reduction of the cell growth and survival. Likewise studies by Xu et al (2011a), Bihrer et al (2011), Marquez et al (2010 have shown that serum levels of miR-21 are increased with a progressive course from chronic hepatitis to cirrhosis and hepatocellular carcinoma. Multivariate analyses demonstrate that the only parameters to be associated with this miRNA are histological necroinflammation and viral load.…”
Section: Mir-21mentioning
confidence: 86%
“…4, C and D). Smad6/7 exhibits antagonistic effects on Smad2/3 phosphorylation (22) and is a direct target of miR-21 (4,5). Antagomir-21 increased Smad7 levels, whereas pre-miR-21 decreased Smad7 expression in both HSC-T6 cells and primary HSCs (Fig.…”
Section: Mir-21 Amplified the Tgf-␤1 Signaling Cascade By Downregulatmentioning
confidence: 93%
“…1F). 4 -treated Mice-To further confirm that miR-21 participated in and promoted the progression of hepatic fibrosis, chemically synthesized antagomirs were administered to knock down miR-21 expression. The miR-21 levels were determined in isolated HSCs from mice after antagomir-21/antago-ctrl treatment.…”
Section: Mir-21 Was Predominantly Up-regulated In Hscs Inmentioning
confidence: 99%
“…MiR-21 has been shown to regulate pro-and antiinflammatory cytokines and has been implicated in the development of fibrosis leading to chronic rejection following liver transplantation. 75,151 This has been also validated in an independent set of HCV+ LT recipients and demonstrated organ specificity (molecular pathways involved in liver injury, malignancy and hepatic disease), and relationship with immune response (T cell lineages development). 150 Farid et al have shown that circulating miR-122, miR-148, miR-194 are sensitive biomarkers for hepatocyte injury and rejection after liver transplantation.…”
Section: Role Of Micrornas In Liver Transplantationmentioning
confidence: 88%
“…74 Recently, Marquez et al analyzed the expression of miR-122 and miR-21 in liver biopsy samples of HCV-infected patients and uninfected controls and found miR-122 levels to be inversely correlated with fibrotic stage, ALT, AST, while miR-21 correlated positively. 75 It was speculated that the dysregulation of miR-21 and miR-122 rather than the expression levels, could be related to fibrosis.…”
Section: Hepatitis Cmentioning
confidence: 99%